The Role of Group 3 Innate Lymphoid Cells in Lung Infection and Immunity - Yang, Dan; Guo, Xinning; Huang, Tingxuan; Liu, Chuntao (Frontiers in Cellular and Infection Microbiology, 2021)
The lung is constantly exposed to environmental particulates such as aeroallergens, pollutants, or microorganisms and is protected by a poised immune response. Innate lymphoid cells (ILCs) are a population of immune cells found in a variety of tissue sites, particularly barrier surfaces such as the lung and the intestine. ILCs play a crucial role in the innate immune system, and they are involved in the maintenance of mucosal homeostasis, inflammation regulation, tissue remodeling, and pathogen clearance. In recent years, group 3 innate lymphoid cells (ILC3s) have emerged as key mediators of mucosal protection and repair during infection, mainly through IL-17 and IL-22 production. Although research on ILC3s has become focused on the intestinal immunity, the biology and function of pulmonary ILC3s in the pathogenesis of respiratory infections and in the development of chronic pulmonary inflammatory diseases remain elusive. In this review, we will mainly discuss how pulmonary ILC3s act on protection against pathogen challenge and pulmonary inflammation, as well as the underlying mechanisms.